Big Data and Learning Analytics: A Big Potential to Improve E-Learning - Khalid Adam, Ismail Hammad; Noor Akma, Abu Bakar; Fakhreldin, Mohammed Adam Ibrahim; Mazlina, Abdul Majid (American Scientific Publisher, 2018)
The learning management systems (LMS) in education sector is widely used and it evolved nowadays. It led to enormous and several of data from the students' activities using online content. It generates a large amount of wasted and unused data these issues cannot be wasted and unused data these issues cannot be processed and supported by the traditional learning analytics. The sophisticated technology of Big Data and also became a recent trend now is vastly evolved relates to data-driven dicision making. It is known as big data analytics and appropriate to apply fpr e-Learning in higher education institution. This paper reviews and explores the impact of Big Data in e-Learning. Big Data Analytics has been proved as an effective approach for education data mining and learning analytics.